Composite materials in automotive industry - a review - Spasenović, Jovana; Blagojević, Ivan (Industrija, 2021)
Composite materials have found extensive use among many industries including automotive. Vehicles are supposed to be lightweight, have low emission and energy consumption to provide some environmental protection while having appropriate stiffness and strength to assure occupant protection. These requirements can be met with the use of composite materials. Although composites have been present in the industry for decades, their use in the automotive sector is moderately new, which requires development in design and manufacturing processes, testing, and recycling - this paper indicates the details by which the automotive industry differs from others. Principal recycling methods, related legislation, and where recycling products are used are described. Specific uses of composite materials that show a high level of innovativeness are indicated – hybrid and natural composites, structural batteries, and high-performance vehicles.